Parameter Uncertainty and the Fiscal Multiplier - Jamie Murray (New Zealand Government, The Treasury, 2013)
I present a simple estimated model of the New Zealand economy which is used to assess the sensitivity of the impact multiplier and output losses associated with fiscal consolidations to uncertainty over model parameters. I find that, in normal times, the fiscal multiplier can be expected to lie between 0.1 and 0.5, with a central estimate of 0.3. Uncertainty over the output effects of fiscal tightening can be attributed to several model parameters and it is found that a bad outcome is likely to be worse than a good outcome is to be better – output risks are skewed to the downside. Sensitivity analysis reveals that if monetary policy in New Zealand were to be constrained by the zero-lower bound, the fiscal impact multiplier would rise substantially, consistent with the empirical evidence for other OECD countries in that position.
Keywords: E62; E43; E32; F33; F41; 330; Fiscal impact multiplier; Ricardian equivalence; DSGE; SVAR; consolidation; monetary policy; uncertainty; lower bound